Overview of the HiLASE project: high average power pulsed DPSSL systems for research and industry. (1st May 2014) - Divoky, M.; Smrz, M.; Chyla, M.; Sikocinski, P.; Severova, P.; Novak, O.; Huynh, J.; Nagisetty, S.S.; Miura, T.; Pilař, J.; Slezak, O.; Sawicka, M.; et al.
Abstract: An overview of the Czech national R&D project HiLASE (High average power pulsed laser) is presented. The project focuses on the development of advanced high repetition rate, diode pumped solid state laser (DPSSL) systems with energies in the range from mJ to 100 J and repetition rates in the range from 10 Hz to 100 kHz. Some applications of these lasers in research and hi-tech industry are also presented.